First Case of Subcutaneous Mycoses Caused by Dirkmeia churashimaensis and a Literature Review of Human Ustilaginales Infections - Hu, Fengming; Wang, Chong; Wang, Peng; Zhang, Lei; Jiang, Qing; Al-Hatmi, Abdullah M. S.; Blechert, Oliver; Zhan, Ping (Frontiers in Cellular and Infection Microbiology, 2021)
Objective Dirkmeia churashimaensis, belonging to Ustilaginales fungi, has never been reported as clinical pathogenic until very recently. In this study, we report an unusual subcutaneous infection with Dirkmeia churashimaensis and reviewed all human Ustilaginales infections. The aim is to better understand their epidemiology, infection type, risk factors, and the sensitivity to antifungal agents. Methods An 80-year-old female farmer developed extensive plaques and nodules on her left arm within 2 years. Pathological and microbiological examinations identified a new pathological agent, Dirkmeia churashimaensis, as the cause of this infection. The patient was successfully cured by oral itraconazole. We reviewed a total of 31 cases of Ustilaginales cases, among of which only three were skin infections. Results Local barrier damage (i.e., surgery, trauma, and basic dermatosis) and systemic immunodeficiency (i.e., preterm and low birthweight, Crohn’s disease, malignant cancer, and chemotherapy) are risk factors for Ustilaginales infection. The D1/D2 and ITS regions are the frequently used loci for identifying the pathogens together with phenotype. Most patients could survive due to antifungal treatment, whereas seven patients died. Amphotericin B, posaconazole, itraconazole, and voriconazole showed good activity against these reported strains, whereas fluconazole, 5-flucytosine, and echinocandins usually showed low susceptibility. Itraconazole had good efficiency for subcutaneous infections. Conclusions The present case study and literature review reveal that Ustilaginales can be opportunistic pathogenic normally in immunocompromised and barrier damage people. A proper identification of fungi can be crucial for clinical treatment, and more data of antifungal are needed for choice of medication against this kind of infections.